The Mildenhall Treasure : Roald Dahl's ultimate tale of the unexpected? - Hobbs, Richard
Just over 50 years ago, the most magnificent treasure of late Antique silver ever found in Britain was brought out of hiding in a sleepy village in rural Suffolk. The late Roald Dahl, the children's writer, may have held the answer.